Does ethnofederalism explain the success of Indian federalism? - Adeney, Katharine (Routledge, 2017)
Ethnofederalism has been contested as a solution for diverse societies as seen recently in Nepal (where federalism has been accepted, but the design and number of units remains heavily contested) and Myanmar (where ethnic minority demands for increasing federalization have had to take a back seat to the demands for increasing democracy). It remains a heavily contested subject in Sri Lanka. Concerns are expressed that ethnofederalism will increase pressures for secession and/or lead to increased violence, through increasing a sense of separateness of the people living within that territory, providing resources for political entrepreneurs to mobilize groups against the center and will lead to the persecution of minorities within the ethnofederal units. India is an example of a federation that appears to demonstrate that ethnofederalism decreases rather than increases conflict through its successful reorganization of states along linguistic lines. However, a group-level analysis reveals a more diverse picture. India has simultaneously been both a success and a failure at conflict management.